2023
DOI: 10.3390/buildings13102574
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Analysis of a New Type of Double-Steering Prestressed Plate Column

Yanying Li,
Bailong Li,
Xinsheng Yin
et al.

Abstract: A new type of dual-steering prestressed plate column is introduced. Compared to the previous prestressed strut column, this proposed column considers both bending and constraints at ends. The calculation results indicated that the support plate significantly improves the stable bearing capacity and buckling performance of the core steel column. When compared to the proposed column, the bearing capacity of the three-transverse prestressed beam column is 1.51 times smaller, the single-transverse prestressed beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Wadee et al [13] suggested a simplified model to estimate the post-buckling behavior of prestressed columns. Li et al [14] introduced a dualsteering-plate-brace prestressed column and conducted modal analyses. However, further studies are required on the elastic-plastic load-bearing capacity and parameter optimization of dual-steering-plate-brace prestressed columns.…”
Section: Introductionmentioning
confidence: 99%
“…Wadee et al [13] suggested a simplified model to estimate the post-buckling behavior of prestressed columns. Li et al [14] introduced a dualsteering-plate-brace prestressed column and conducted modal analyses. However, further studies are required on the elastic-plastic load-bearing capacity and parameter optimization of dual-steering-plate-brace prestressed columns.…”
Section: Introductionmentioning
confidence: 99%